Molecular Evaluation of Genetic Diversity in Wild-Type Mastic Tree (Pistacia lentiscus L.) - ALTINKUT UNCUOĞLU, AHU; AYDİN, YILDIZ (SPRINGER/PLENUM PUBLISHERS, 2016)
In this study, the patterns of genetic variation and phylogenetic relationships of mastic tree (Pistacia lentiscus L.) genotypes including 12 males and 12 females were evaluated using SSR, RAPD, ISSR, and ITS markers yielding 40, 703, 929 alleles, and 260-292 base pairs for ITS1 region, respectively. The average number of alleles produced from SSR, RAPD, and ISSR primers were 5.7, 14, and 18, respectively. The grouping pattern obtained from Bayesian clustering method based on each marker dataset was produced. Principal component analyses (PCA) of molecular data was investigated and neighbor joining dendrograms were subsequently created. Overall, the results indicated that ISSR and RAPD markers were the most powerful to differentiate the genotypes in comparison with other types of molecular markers used in this study. The ISSR results indicated that male and female genotypes were distinctly separated from each other. In this frame, M9 (Ala double dagger atA+/-) and M10 (Mesta SakA+/-z AdasA+/--Chios) were the closest genotypes and while F11 (Seferihisar) and F12 (Bornova/Gokdere) genotypes fall into same cluster and showing closer genetic relation. The RAPD pattern indicated that M8 (Urla) and M10 (Mesta SakA+/-z AdasA+/--Chios), and F10 (Mesta SakA+/-z AdasA+/--Chios) and F11 (Seferihisar) genotypes were the closest male and female genotypes, respectively.
Keywords: DNA markers; Genetic diversity; Phylogenetic relationship; Population structure; Principle component analysis; POLYMORPHIC DNA RAPD; MICROSATELLITE MARKERS; SEX DETERMINATION; ANACARDIACEAE; VERA; CULTIVARS; ISSR; IDENTIFICATION; PHYLOGENY; GERMPLASM